Upaya Peningkatan Kompetensi Guru dalam Pembelajaran melalui Supervisi Kelas pada TK PKK Terpadu Mayang Nira Selong Kecamatan Selong Tahun Pelajaran 2020/2021 - Hairi, Hj. (MASALIQ, 2021)
This school action research activity was carried out at the PKK Terpadu Mayang Nira Selong Kindergarten for 3 months, starting from August to October 2020 by going through cycle stages. The purpose of this school action research (PTS) is to determine the extent to which the supervision carried out by the principal followed by the provision of guidance/treatment to the target teachers can improve the competence of these teachers in applying learning models in the classroom. In this school action research (PTS) it was conducted in 2 cycles, from the results of the actions taken it was proven to be able to increase teacher competence by achieving ideal standards. In the first cycle, the increase in teacher competence after classroom supervision was carried out after coaching on the use of several new learning models reached around 33.33% in the second cycle, it could increase to 100%. The average score obtained after class supervision was carried out in the first cycle was 63.00 and increased in the second cycle to 83.33, meaning that there was an increase of 20.33. The results of this school action research show that coaching principals can improve teacher competence in developing learning by applying learning models in their respective classes.